Crystal structure determination of non-stoichiometric Ca4−xRuO6−x (x = 1.17) from X-ray powder diffraction data. Issue 1 (17th February 2016) - Etter, Martin; Krautloher, Maximilian J.; Sung, Nakheon; Bertinshaw, Joel; Kim, Bumjoon; Dinnebier, Robert E.
Abstract : A new non-stoichiometric calcium ruthenate [Ca4− x RuO6− x with x = 1.17(1)] was synthesized by the flux growth method and characterized by the X-ray powder diffraction. The crystal structure is isostructural to the K4 CdCl6 type with space group R 3 c . Unit-cell parameters are a = 9.2881(1), c = 11.1634(2) Å, V = 834.03(3) Å 3, and Z = 6.